2016
DOI: 10.1080/23306343.2016.1182238
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based exploration into the effect of language-pair specificity in English-Chinese simultaneous interpreting

Abstract: Whether and how language-pair specificity affects the process and product of interpreting is a recurring implicit topic of debate in interpreting studies. Previous discussions have touched upon this issue in Japanese/English and German/English interpreting, with little attention to its role in Chinese/English interpreting. This study focuses on the effect of structural asymmetry between English and Chinese on English-Chinese simultaneous interpreting performance, which is exemplified by right-branching structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Striking differences between English and Chinese at lexical, syntactical, and discourse levels (Chen, 2015) may cause extra difficulties in interpreting. Data collected from real-time measurement and/or product analysis have demonstrated that word order asymmetry is a major obstacle during English/Chinese interpreting: The processing of asymmetric structures causes more frequent errors and disfluencies (Wang & Gu, 2016), a considerable increase in cognitive effort (Ma et al, 2021), and specific strategies (Dawrant, 1996;Guo, 2011). This asymmetry impact may be exacerbated in interpreting from Chinese into English.…”
Section: Word Order Asymmetry In Chinese/english Interpretingmentioning
confidence: 99%
“…Striking differences between English and Chinese at lexical, syntactical, and discourse levels (Chen, 2015) may cause extra difficulties in interpreting. Data collected from real-time measurement and/or product analysis have demonstrated that word order asymmetry is a major obstacle during English/Chinese interpreting: The processing of asymmetric structures causes more frequent errors and disfluencies (Wang & Gu, 2016), a considerable increase in cognitive effort (Ma et al, 2021), and specific strategies (Dawrant, 1996;Guo, 2011). This asymmetry impact may be exacerbated in interpreting from Chinese into English.…”
Section: Word Order Asymmetry In Chinese/english Interpretingmentioning
confidence: 99%
“…In terms of fluency error, we see that ED-type interpreters produce the least errors, followed by EIB and ID (p<.01), as shown in Figure 9. One possible explanation for this result would be the differences in the grammatical structure between English and Chinese (Wang & Gu, 2016). ED-type interpreters follow the flow of the source speech more closely, which usually involves a higher degree of deverbalization, and thus may contribute to their higher level of fluency.…”
Section: Relationship Between Attention Patterns and Simtxt Qualitymentioning
confidence: 99%
“…The RC is a frequently discussed structure in the literature on structural asymmetry between Chinese and English (Setton 1999;Wang and Gu 2016;Wang and Zou 2018). The two languages differ in their use of RCs.…”
Section: Structures Analyzedmentioning
confidence: 99%